Sales gallery adaptive reuse feasibility study into Indoor Hawker Centre in Penang (ARTEKS : Jurnal Teknik Arsitektur, 2025)
In the built environment, recycling can be practiced through a method known as "Adaptive Reuse" (AR). AR is an alternative to “recycling the existing structure”, which significantly reduce the pollution and greenhouse gas generated during construction, seen from sustainable development aspects. It could be a strategy to achieve sustainable development goal, which repurpose a abandoned building based on the pubic demand. It is worth noting that the architectural aspects of a building are influencing the adaptive reuse decision, but the lack of previous studies cast a doubt on such transformation. This study examines the feasibility of converting a sales gallery in Penang into a hawker centre, with a primary objective, which is to explore the perceptions of related practitioners about the AR feasibility transforming sales gallery into indoor hawker centre on architectural aspects. The qualitative primary data of the research will be gathered through case study interviews with practitioners from diverse field related to build environment or food and beverage interior design expertise. Their perspectives on repurposing the chosen case study into a hawker centre, addressing site context and architectural aspects will be revealed through qualitative findings.
Keywords: Adaptive reuse; Feasibility study; Indoor Hawker Centre; Sales gallery and Penang